Abrupt climate change as an important agent of ecological change in the Northeast US throughout the past 15,000 years - Shuman, B. N.; Newby, P.; Donnelly, J. P. (Quaternary Science Reviews, 2009)
We use a series of tests to evaluate two competing hypotheses about the association of climate and vegetation trends in the northeastern United States over the past 15 kyrs. First, that abrupt climate changes on the scale of centuries had little influence on long-term vegetation trends, and second, that abrupt climate changes interacted with slower climate trends to determine the regional sequence of vegetation phases. Our results support the second. Large dissimilarity between temporally close fossil pollen samples indicates large vegetation changes within 500 years across >4 degrees of latitude at ca 13.25-12.75, 12.0-11.5, 10.5, 8.25, and 5.25 ka. The evidence of vegetation change coincides with independent isotopic and sedimentary indicators of rapid shifts in temperature and moisture balance. In several cases, abrupt changes reversed long-term vegetation trends, such as when spruce (Picea) and pine (Pinus) pollen percentages rapidly declined to the north and increased to the south at ca 13.25-12.75 and 8.25 ka respectively. Abrupt events accelerated other long-term trends, such as a regional increase in beech (Fagus) pollen percentages at 8.5-8.0 ka. The regional hemlock (Tsuga) decline at ca 5.25 ka is unique among the abrupt events, and may have been induced by high climatic variability (i.e., repeated severe droughts from 5.7 to 2.0 ka); autoregressive ecological and evolutionary processes could have maintained low hemlock abundance until ca 2.0 ka. Delayed increases in chestnut (Castanea) pollen abundance after 5.8 and 2.5 ka also illustrate the potential for multi-century climate variability to influence species' recruitment as well as mortality. Future climate changes will probably also rapidly initiate persistent vegetation change, particularly by acting as broad, regional-scale disturbances. (C) 2009 Published by Elsevier Ltd.
id: 1892; ISI Document Delivery No.: 484ZD Times Cited: 3 Cited Reference Count: 112 Cited References: *COHMAP MEMB, 1988, SCIENCE, V241, P1043 ADGER N, 2007, CLIMATE CHANGE 2007 ALLEY RB, 1997, GEOLOGY, V25, P483 ALLEY RB, 2000, QUATERNARY SCI REV, V19, P213 ALLISON TD, 1986, ECOLOGY, V67, P1101 ALMQUISTJACOBSON H, 1995, VEG HIST ARCHAEOBOT, V4, P211 ANDERSON RS, 1986, CAN J BOT, V64, P1977 ANDERSON RS, 1992, BOREAS, V21, P359 BARBER DC, 1999, NATURE, V400, P344 BARTLEIN PJ, 1995, QUATERNARY RES, V44, P417 BEISNER BE, 2003, FRONT ECOL ENVIRON, V1, P376 BENNETT KD, 2002, HOLOCENE, V12, P421 BHIRY N, 1996, QUATERNARY RES, V45, P312 BIGLER C, 2007, OIKOS, V116, P1983, DOI 10.1111/j.2007.0030-1299.16034.x BOAG PT, 1981, SCIENCE, V214, P82 BOND G, 1997, SCIENCE, V278, P1257 CALCOTE R, 2003, HOLOCENE, V13, P215, DOI 10.1191/0959683603hl608rp CLARK JS, 1995, HOLOCENE, V5, P1 CLARK JS, 1996, ECOLOGY, V77, P2148 CLARK PU, 2001, SCIENCE, V293, P283 CWYNAR LC, 1995, QUATERNARY RES, V43, P405 CWYNAR LC, 2001, QUATERNARY SCI REV, V20, P1265 DAVIS MB, 1969, ECOLOGY, V50, P409 DAVIS MB, 1981, P 4 INT PAL C LUCKN, V3, P216 DAVIS MB, 1985, QUATERNARY RES, V23, P327 DAVIS MB, 1989, CLIMATIC CHANGE, V15, P75 DAVIS MB, 2005, ECOLOGY, V86, P1704 DAVIS RB, 1975, QUATERNARY RES, V5, P436 DEEVEY ES, 1939, AM J SCI, V237, P691 DELCOURT HR, 1994, J BIOGEOGR, V21, P137 DIEFFENBACHERKRALL AC, 2005, J PALEOLIMNOL, V34, P283, DOI 10.1007/s10933-005-4958-8 EWING HS, 2000, THESIS U MINNESOTA FAISON EK, 2006, ECOLOGY, V87, P2537 FOSTER D, 2003, BIOSCIENCE, V53, P77 FOSTER DR, 1993, ECOLOGY, V74, P982 FOSTER DR, 1998, ECOSYSTEMS, V1, P96 FOSTER DR, 2002, J BIOGEOGR, V29, P1359 FOSTER DR, 2006, ECOLOGY, V87, P2959 FULLER JL, 1998, ECOLOGY, V79, P2337 FULLER JL, 1998, ECOSYSTEMS, V1, P76 GAUDREAU DC, 1985, POLLEN RECORDS LATE, P247 GAUDREAU DC, 1986, LATE QUATERNARY VEGE GRAY ST, 2006, ECOLOGY, V87, P1124 GREEN DG, 1982, J BIOGEOGR, V9, P29 GRIMM EC, 1992, CLIM DYNAM, V6, P179 HAAS JN, 1999, S SUST MAN HEML ECOS, P81 HOU J, 2007, GEOPHYS RES LETT, V34, ARTN L19706 HOU J, 2009, DATA CONTRIBUTION SE HOU JZ, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q03008 HUANG YS, 2002, GEOLOGY, V30, P1103 JACKSON ST, 2002, DIVERS DISTRIB, V8, P275 JACKSON ST, 2004, ANNU REV EARTH PL SC, V32, P495, DOI 10.1146/annurev.earth.32.101802.120435 JOHNSON WC, 1989, J BIOGEOGR, V16, P561 KASHIAN DM, 2005, ECOLOGY, V86, P643 KELLOGG DC, 1991, PREHISTORIC LANDSCAP KUREK J, 2004, QUATERNARY SCI REV, V23, P627, DOI 10.1016/S0277-3791(03)00211-7 KURZ WA, 2008, NATURE, V452, P987, DOI 10.1038/nature06777 LEOPOLD EB, 1956, P NATL ACAD SCI USA, V52, P863 LEVESQUE AJ, 1997, NATURE, V385, P423 LEVIN DA, 1984, AM J BOT, V71, P1040 LI YX, 2007, HOLOCENE, V17, P3, DOI 10.1177/0959683606069386 LINDBLADH M, 2007, QUATERNARY RES, V67, P502, DOI 10.1016/j.yqres.2007.01.010 LYFORD ME, 2003, ECOL MONOGR, V73, P567 MAENZAGMELCH TE, 1997, HOLOCENE, V7, P25 MAENZAGMELCH TE, 1997, J QUATERNARY SCI, V12, P15 MARLON JR, 2009, P NATL ACAD SCI USA, V106, P2519, DOI 10.1073/pnas.0808212106 MAYLE FE, 1995, ECOL MONOGR, V65, P130 MCLAUCHLAN KK, 2007, P NATL ACAD SCI USA, V104, P7466, DOI 10.1073/pnas.0701779104 MOTT RJ, 1977, GEROGR PHYS QUATERN, V31, P139 MOTT RJ, 1986, NATURE, V323, P247 MULLER SD, 2003, PALAEOGEOGR PALAEOCL, V193, P51, DOI 10.1016/S0031-0182(02)00710-1 NEWBY PE, 2000, QUATERNARY RES, V53, P352 OSWALD WW, 2007, J BIOGEOGR, V34, P900, DOI 10.1111/j.1365-2699.2006.01650.x OVERPECK JT, 1985, QUATERNARY RES, V23, P87 PAINE RT, 1998, ECOSYSTEMS, V1, P535 PARSHALL T, 2002, J BIOGEOGR, V29, P1305 PARSHALL T, 2003, ECOLOGY, V84, P736 PETEET DM, 1990, QUATERNARY RES, V33, P219 PRENTICE IC, 1991, ECOLOGY, V72, P2038 REIMER PJ, 2004, RADIOCARBON, V46, P1029 ROBINSON GS, 2005, ECOL MONOGR, V75, P295 SHEMESH A, 1998, GEOPHYS RES LETT, V25, P1935 SHUMAN B, 2001, QUATERNARY RES, V56, P401 SHUMAN B, 2001, THESIS BROWN U SHUMAN B, 2002, QUATERNARY SCI REV, V21, P1777 SHUMAN B, 2002, QUATERNARY SCI REV, V21, P1793 SHUMAN B, 2004, ECOLOGY, V85, P1297 SHUMAN B, 2005, ANN ASSOC AM GEOGR, V95, P237 SHUMAN B, 200 , QUATERNARY SCI REV, V24, P2194, DOI 10.1016/j.quascirev.2005.03.018 SHUMAN B, 2006, QUATERNARY RES, V65, P44, DOI 10.1016/j.yqres.2005.09.001 SHUMAN B, 2006, QUATERNARY SCI REV, V25, P2992, DOI 10.1016/j.quascirev.2006.02.021 SHUMAN B, 2007, QUATERNARY SCI REV, V26, P268, DOI 10.1016/j.quascirev.2006.08.009 SPEAR RW, 1994, ECOL MONOGR, V64, P85 STJACQUES JM, 2000, J PALEOLIMNOL, V23, P385 SUTER SM, 1985, CURRENT RES PLEISTOC, V2, P87 TELFORD RJ, 2004, QUATERNARY SCI REV, V23, P1, DOI 10.1016/j.quascirev.2003.11.003 TZEDAKIS PC, 1992, GEROGR PHYS QUATERN, V46, P113 VANMANTGEM PJ, 2009, SCIENCE, V323, P521, DOI 10.1126/science.1165000 VIAU AE, 2007, QUATERNARY SCI REV, V26, P264, DOI 10.1016/j.quascirev.2006.07.010 WEBB T, 1982, 3RD P N AM PAL CONV, V2, P569 WEBB T, 1986, VEGETATIO, V67, P75 WHITE PS, 1985, ECOLOGY NATURAL DIST, P3 WHITEHEAD DR, 1978, POL ARCH HYDROBIOL, V25, P471 WHITEHEAD DR, 1979, QUATERNARY RES, V12, P333 WHITMORE J, 2005, QUATERNARY SCI REV, V24, P1828, DOI 10.1016/j.quascirev.2005.03.005 WILLIAMS JW, 2002, GEOLOGY, V30, P971 WILLIAMS JW, 2004, ECOL MONOGR, V74, P309 WILLIAMS JW, 2006, ATLAS POLLEN VEGETAT WILLIAMS JW, 2008, QUATERNARY SCI REV, V27, P669, DOI 10.1016/j.quascirev.2008.01.004 WINKLER MG, 1985, QUATERNARY RES, V23, P301 YU ZC, 1997, GEOLOGY, V25, P251 YU ZC, 2007, QUATERNARY RES, V67, P297, DOI 10.1016/j.yqres.2006.08.006 Shuman, Bryan N. Newby, Paige Donnelly, Jeffrey P. Pergamon-elsevier science ltd Oxford Sp. Iss. SI; YY